Pengaruh Pengetahuan Keuangan Terhadap Pengelolaan Keuangan Keluarga Dengan Gaya Hidup Sebagai Variabel Moderasi (Study Kasus Di Masyarakat Kecamatan Tidore Timur) - Hadi, Muksin; Hadady, Hartaty; Amiro, Suratno; Pratama, Rheza (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
The aims of this study were: (1) to find out and analyze the effect of financial knowledge on family financial management in the people of the East Tidore sub-district. (2) To find out and analyze the effect of financial knowledge on financial management moderated by lifestyle. The number of samples in this study were 100 respondents from family members in the East Tidore sub-district. The test tool used is simple linear regression analysis using the statistical package for social scientists (SPSS) 25 as a statistical test tool. The results of the study show that: (1) Financial knowledge influences family financial management in the East Tidore sub-district community; and (2) Lifestyle influences and strengthens financial knowledge on family financial management in the East Tidore sub-district community